1, 2, 4-Triazole-3-Thiones: Greener, One-Pot, Ionic Liquid Mediated Synthesis and Antifungal Activity. (2nd January 2023) - Hassan, Mohd. Zaheen; Alsayari, Abdulrhman; Asiri, Yahya I.; Bin Muhsinah, Abdullatif
Abstract: Herein, we describe an efficient and rapid protocol for the synthesis of hitherto unreported 5-(benzothiazol-2-ylmethyl)-4-aryl-1, 2, 4-triazole-3-thiones by a one-pot condensation of 2-(benzothiazole-2-yl)acetohydrazide and aryl isothiocyanate in the presence of a base in the ionic liquid [bmim]Br. Among the eleven newly synthesized hybrid benzothiazolyl-triazole analogues, 5-(benzothiazol-2-ylmethyl)-4-(4-chlorophenyl)-2, 4-dihydro-3H-1, 2, 4-triazole-3-thione (3d ) displayed promising antifungal activity with MIC values of 12.5 and 0.39 μg/mL against the Aspergillus fumigatus and Candida albicans, respectively. Molecular docking studies employing CYP51 was also carried out to evaluate the binding mode of the most potent triazole derivative.